EGb761 suppressed vascular dementia via modulating Wnt/β-catenin signaling pathway-induced apoptosis and autophagy in hippocampal neuronal cells - Nan Yin; Zhipeng Tang; Yanyan Yang; Xiuqin Li; Ruisheng Duan; Guodong Xu; Peiyuan Lv (European Journal of Medical Research)
Abstract Objectives The study aimed to explore the effects of EGb761 on vascular dementia (VD) rats and the mechanisms of action. Methods The Morris water maze test was utilized to assess the spatial learning and memory abilities of the rats; Hematoxylin and Eosin (HE) staining and electron microscopy were used to observe changes in hippocampal neuron cells; Immunohistochemistry was performed to detect the expression of cleaved caspase-3 and microtubule-associated proteins light chain 3 (LC3-II) positive cells in hippocampal neurons; immunofluorescence staining was carried out to determine the immunofluorescence intensity of IRGM in hippocampal neurons; western blotting was used to measure the expression of related proteins. Results EGb761 significantly improved the cognitive function of vascular dementia rats (P < 0.01) and reduced the apoptosis of hippocampal neurons.Furthermore, EGb761 suppressed ROS, thereby promoting the expression of proteins related to the Wnt/β-catenin signaling pathway and inhibiting the expression of C-Jun N-terminal Kinase (p-JNK), c-Jun N-terminal kinase (p-c-JUN), Protein 53 (P53), immunity-related GTPase M (IRGM), Transcription Factor EB (TFEB), microtubule-associated proteins light chain 3 (LC3), Lysosomal Associated Membrane Protein 1 (LAMP1), and Sequestosome 1 (SQSTM1). Conclusions Ginkgo Biloba Extract 761 (EGb761) mediated the Wnt/β-catenin signaling pathway to inhibit apoptosis and autophagy in hippocampal neurons in VD rats.